Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Disiplin Kerja Guru dan Pegawai di SMP PGRI 03 Kencong Jember - Nuriyah Fikri Wahyuni; Siti Fatikhah Nur Aini; Umul Ulfa Mufida; Abdul Muhith (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2021)
This study aims to identify and describe the role of principal leadership in improving the work discipline of teachers and employees and to find out what obstacles are the obstacles to the role of principal leadership in improving the work discipline of teachers and employees at SMP PGRI 03 Kencong, Jember Regency. Is a type of qualitative descriptive research and uses purposive sampling technique. There are five roles of the Principal and two obstacles faced by the Principal in improving the work discipline of teachers and employees. The results showed that the principal of SMP PGRI 03 Kencong, Jember Regency carried out the role of a leader by planning and deliberating; as a manager by creating collaboration between teachers and employees; as an educator by preparing a learning program plan; as an administrator by managing facilities and infrastructure as well as financial administration; motivator by providing motivation with a conducive school environment. The obstacles faced by the principal in improving the work discipline of teachers and employees are teachers and employees who are less disciplined in carrying out their duties so that it is also difficult to improve their work discipline, as well as obstacles in inadequate school facilities and infrastructure. Keywords: employees, leadership, principals, teachers, work discipline Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan peran kepemimpinan kepala sekolah dalam meningkatkan disiplin kerja guru dan pegawai dan untuk mengetahui kendala apa saja yang menjadi penghambat peran kepemimpinan kepala sekolah dalam meningkatkan disiplin kerja guru dan pegawai di SMP PGRI 03 Kencong Kabupaten Jember. Penelitian ini merupakan jenis penelitian deskriptif kualitatif dan menggunakan teknik Purposive Sampling. Terdapat lima peran Kepala Sekolah dan dua kendala yang dihadapi oleh Kepala Sekolah dalam meningkatkan disiplin kerja guru dan pegawai. Dari hasil penelitian menunjukkan bahwa kepala sekolah SMP PGRI 03 Kencong Kabupaten Jember melaksanakan peran sebagai pemimpin dengan membuat perencanaan dan bermusyawarah; sebagai manajer dengan menciptakan kerjasama antara guru dan pegawai; sebagai pendidik dengan menyusun rencana program pembelajaran;sebagai administrator dengan mengelola sarana dan prasarana serta administrasi keuangan; motivator dengan memberikan motivasi dengan lingkungan sekolah yang kondusif. Kendala yang dihadapi kepala sekolah dalam meningkatkan disiplin kerja guru dan pegawai yaitu guru dan pegawai yang kurang disiplin dalam melaksanakan tugas sehingga kesulitan pula dalam meningkatkan disiplin kerjanya, serta kendala dalam sarana dan prasarana sekolah yang belum memadai. Kata Kunci: disiplin kerja, guru, kepemimpinan, kepala sekolah, pegawai